(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The hotel sector is one of the most vital sectors exposed to risks, and the authorities concerned with control must take their active and influential role in putting the hotel sector on the right track and compatible with the internationally approved approaches, and the importance of auditing the performance of the hotel sector in light of the (Covid-19) pandemic is embodied in the fact that it gives a clear and realistic picture to the management and regulatory bodies about the performance and activities of this sector and the shortcomings and deviations that must be addressed, and also helps government decision makers to obtain appropriate information about the performance and activities of this The sector and the extent to which it can develop its performance in the future , Therefore, the research sought to identify the (Covid-19) pandemic that occurred during the research period and its reflection on the performance of the hotel Research sample, as well as to identify the reality of auditing the hotel Research sample and develop indicators to measure the performance of the sector and identify its reflection on the result of the activity, and the research problem lies in the impact of the (Covid-19) pandemic on the hotel sector, which was represented in the decline in revenues derived from the operational activities it performs, as this pandemic led to a weak turnout of customers to the hotel, which was reflected On the percentage of accommodation in hotel rooms and revenues derived from services provided to guests, The research was based on the premise that the outbreak of the (Covid-19) pandemic affects hotel performance and is reflected as a result of the activity, and the research reached several conclusions, the most important of which is that during the year 2020, the impact of the (Covid-19) pandemic was reflected on the performance of the hotel The research sample and the result of its activity, as the room occupancy rate reached its lowest level compared to other years under research due to the weak turnout of Iraqi guests as a result of the imposition of a curfew in Iraq, as well as the lack of turnout of guests from outside Iraq, especially in The second and third quarters of the year due to the strict measures of most countries, which resulted in the closure of airports and the suspension of flights to other countries, and the research reached several recommendations, the most important of which is the need for the hotel management to conduct a serious study to find alternative investment opportunities that contribute to increasing the hotel’s resources, which would reduce the impact of such a pandemic on the result of the activity.